2020
DOI: 10.1111/mec.15487
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota of invasive bullfrog tadpoles responds more rapidly to temperature than a noninvasive congener

Abstract: Environmental temperature can alter the composition, diversity, and function of ectothermic vertebrate gut microbial communities, which may result in negative consequences for host physiology, or conversely, increase phenotypic plasticity and persistence in harsh conditions. The magnitude of either of these effects will depend on the length of time animals are exposed to extreme temperatures, and how quickly the composition and function of the gut microbiota can respond to temperature change. However, the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 92 publications
3
32
1
Order By: Relevance
“…Environmental temperature can alter microbial taxonomic community and predicted microbial function, resulting in increased phenotypic plasticity and persistence in harsh conditions (Fontaine & Kohl, 2020b). For example, gut microbiota of invasion bullfrog tadpoles responds more rapidly to environmental temperature than noninvasion green frogs (Fontaine & Kohl, 2020b). Environmental temperature alters the digestive performance and gut microbiota of red-backed salamanders ( Plethodon cinereus : Fontaine, Novarro, & Kohl, 2018) and in a study of western clawed frogs ( Xenopus tropicalis ) the authors observed a higher prevalence of Verrucomicrobia in the gut of frogs inhabiting a warmer environment, and an opposite pattern in Proteobacteria (J.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Environmental temperature can alter microbial taxonomic community and predicted microbial function, resulting in increased phenotypic plasticity and persistence in harsh conditions (Fontaine & Kohl, 2020b). For example, gut microbiota of invasion bullfrog tadpoles responds more rapidly to environmental temperature than noninvasion green frogs (Fontaine & Kohl, 2020b). Environmental temperature alters the digestive performance and gut microbiota of red-backed salamanders ( Plethodon cinereus : Fontaine, Novarro, & Kohl, 2018) and in a study of western clawed frogs ( Xenopus tropicalis ) the authors observed a higher prevalence of Verrucomicrobia in the gut of frogs inhabiting a warmer environment, and an opposite pattern in Proteobacteria (J.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that even though environmental isothermality and lungworm infection intensity are not significantly different between range-core and invasion-front toads, environmental isothermality and occurrence of lungworms are significantly associated with the microbial taxonomic community and predicted microbial function. Environmental temperature can alter microbial taxonomic community and predicted microbial function, resulting in increased phenotypic plasticity and persistence in harsh conditions (Fontaine & Kohl, 2020b). For example, gut microbiota of invasion bullfrog tadpoles responds more rapidly to environmental temperature than noninvasion green frogs (Fontaine & Kohl, 2020b).…”
Section: Associations Between Gut Microbiota Environmental Isothermamentioning
confidence: 99%
See 2 more Smart Citations
“…One potential application is to measure the impact of microorganisms in vertebrate adaptation and improve predictions from anthropogenic disturbances, such as climate change and habitat destruction, on species distributions. It has been proposed that metagenomes could confer enhanced adaptive capacity to their hosts ( Alberdi et al., 2016 ), potentially enabling rapid adaptation to changing environmental conditions ( Fontaine and Kohl, 2020 ). The adaptive capacity of hosts and their associated microbiota through linking specific host genotypes with metagenomes has been demonstrated with regard to toxicity resilience ( Macke et al., 2017 ), heat tolerance ( Moran and Yun, 2015 ), drought and desiccation ( Cernava et al., 2019 ), disease resistance ( Rosshart et al., 2017 ), and nutrient acquisition ( Falcinelli et al., 2015 ).…”
Section: Applying the Holo-omic Approach Across Biological Sciencesmentioning
confidence: 99%